2021
DOI: 10.7150/ijbs.62752
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin and trametinib: a rational combination for treatment of NSCLC

Abstract: Mammalian target of rapamycin (mTOR) is one of the most commonly activated pathways in human cancers, including lung cancer. Targeting mTOR with molecule inhibitors is considered as a useful therapeutic strategy. However, the results obtained from the clinical trials with the inhibitors so far have not met the original expectations, largely because of the drug resistance. Thus, combined or multiple drug therapy can bring about more favorable clinical outcomes. Here, we found that activation of ERK pathway was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Chen et al ( 47 ) showed that rapamycin greatly enhanced dasatinib-induced cell growth inhibition and cell cycle G1 arrest in human lung adenocarcinoma A549 cells, without affecting apoptosis. Sun et al ( 48 ) demonstrated that a combination of rapamycin and trametinib could more effectively inhibit NSCLC cell viability and proliferation. The reason for this discrepancy between the results of the present study and those of the aforementioned two studies may be that rapamycin used alone to treat cells mainly activates the autophagy pathway, while synergistic action with other anticancer drugs affects other pathways, thus leading to different results.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 47 ) showed that rapamycin greatly enhanced dasatinib-induced cell growth inhibition and cell cycle G1 arrest in human lung adenocarcinoma A549 cells, without affecting apoptosis. Sun et al ( 48 ) demonstrated that a combination of rapamycin and trametinib could more effectively inhibit NSCLC cell viability and proliferation. The reason for this discrepancy between the results of the present study and those of the aforementioned two studies may be that rapamycin used alone to treat cells mainly activates the autophagy pathway, while synergistic action with other anticancer drugs affects other pathways, thus leading to different results.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs were administrated daily through intraperitoneal injection for 18 days. Treatment conditions were chosen as previously reported 34,37–39 . Tumour volume was calculated using the formula: V = ( L × W 2 )/2.…”
Section: Methodsmentioning
confidence: 99%
“…Treatment conditions were chosen as previously reported. 34,[37][38][39] Tumour volume was calculated using the formula:…”
Section: Methylated Rna Immunoprecipitationmentioning
confidence: 99%
“…All cell lines were cultured in RPMI-1640 medium (Gibco, United States), supplemented with 10% FBS (Gibco, United States), and maintained at 37°C in a standard incubator (5% CO 2 ). In addition, abemaciclib-resistant A549 cells were developed through serial passaging with dose-escalation of abemaciclib for 3 months by continuous drug exposure ( Pesch et al, 2020 ; Sun et al, 2021b ).…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was measured as described previously ( Sun et al, 2021b ). Briefly, cells were seeded into 96-well plates at 4,000 cells per well, and continuously cultured for 24 h. Then, cells were treated with abemaciclib or gilteritinib alone, or in combination.…”
Section: Methodsmentioning
confidence: 99%